IMPLICATIONS OF THE USE OF ARTIFICIAL INTELLIGENCE IN MANAGEMENT ACCOUNTING: A LITERATURE REVIEW - Henny Rakhmawati; Umarudin Kurniawan; Agus Prasetyo (Adisam Publisher, 2024)
The use of artificial intelligence (AI) technology has grown in importance as a ever-growing digital era. AI is able to provide more accurate and quality analysis for faster processing times, AI is able to offer higher efficiency and lower long-term costs to companies. In the field of management accounting, AI offers a lot of promise to increase the effectiveness and precision of commercial decision-making. Modern management accounting includes managing internal financial data processing as well as external financial data processing in the age of artificial intelligence company finances. The use of AI can help management accountants to produce quality information and AI can also help in the decision-making process by providing recommendations based on historical data and market trends so that management accountants have accurate information to manage company finances. Although AI has many benefits and can help in many aspects of management accounting, AI cannot replace the main role of humans, especially in decision-making. AI won't be able to fully replace management accounting experts, at least not in the near future, since AI cannot take the position of human creativity and emotion-based thinking. AI related to management accounting is a new area for business. Effective and ethical implementation is key to maximizing benefits while minimizing negative impacts.